Avβ3 Single-Stranded DNA Aptamer Attenuates Vascular Smooth Muscle Cell Proliferation and Migration via Ras-PI3K/MAPK Pathway - Hong-Bing Wu; Zhi-Wei Wang; Feng Shi; Zong-Li Ren; Luo-Cheng Li; Xiao-Ping Hu; Rui Hu; Bo-Wen Li (Cardiovascular Therapeutics)
Objectives. To observe the effect of avβ3 single-stranded (ss) DNA on proliferation and migration of vascular smooth muscle cells (VSMCs) and its potential mechanism. Background. Percutaneous transluminal coronary angioplasty (PTCA) is currently the preferred method for the treatment of coronary heart disease. However, vascular restenosis still occurs after PTCA treatment, severely affecting the clinical efficacy of PTCA. Integrin avβ3, which is widely expressed on various cell surfaces, plays an important role in the proliferation and migration of VSMCs. Methods. In this experiment, we used systematic evolution of ligands by exponential enrichment (SELEX) to screen out avβ3 ssDNA, which has high affinity and specificity to the avβ3 protein. MTT, Transwell, and cell scratch assays were carried out to examine the effect of avβ3 ssDNA on the proliferation and migration of VSMCs. Flow cytometry was performed to detect apoptosis and cell cycle progression. The effect of avβ3 ssDNA on the Ras-phosphatidylinositol-4,5-bisphosphate 3-kinase/mitogen-activated protein kinase (PI3K/MAPK) signaling pathway was evaluated by quantitative reverse transcription polymerase chain reaction and western blot. Results. In the present study, we found that avβ3 ssDNA significantly decreased the expression of osteopontin, focal adhesion kinase, Ras, p-PI3K, and p-MAPK at both mRNA and protein levels (P<0.05). Avβ3 ssDNA also inhibited VSMC proliferation and migration while promoting apoptosis (P<0.05), as demonstrated by the upregulation of the proapoptotic proteins Bax and active caspase 3 (P<0.05). Conclusions. The findings suggest that avβ3 ssDNA inhibited the proliferation and migration of VSMCs by suppressing the activation of Ras-PI3K/MAPK signaling.